DEVELOPMENT OF RENEWABLE ENERGY SOURCES IN THE CONTEXT OF ENERGY MANAGEMENT - YAKUBIV, VALENTYNA; MAKSYMIV, YULIIA; HRYHORUK, IRYNA; POPADYNETS, NAZARIY; PIATNYCHUK, IRYNA (Journal of Vasyl Stefanyk Precarpathian National University, 2019)
The paper deals with global trends in energy consumption and renewable energy generation. Worldwide practices in financing of renewable energy production are analysed according to the following dimensions: sources of financing, types of used policy instruments, types of recipients (public or private) and types of financed technologies. The key factors that influence the investment attractiveness of renewable energy sources in the world are presented. Main obstacles impeding the utilisation of potential of renewable energy generation in Ukraine are pointed out from the standpoint of the global development trends, as the experience of economically developed countries are advised to be used for Ukraine. Conditions for investment activity in this field should be created (involving both domestic and foreign investments), stimulating state policy should be implemented, and an energy management based on the international experience should be developed. The problems of renewable energy sources in Ukraine are described, in particular, the presence of investment risk in terms of its components as general economic, legal and financial. In the most developed countries in terms of RES consumption direct public investment is a small proportion of total renewable energy financing, whereas private investment has the major share. A significant obstacle to the possibility of realizing such experience in Ukraine is the presence of investment risk, mainly caused by unstable political conditions (both internal and external). Energy management and monitoring activities of enterprises of various forms of ownership and branch affiliation should be introduced along with the necessity of attracting investments in renewable energy. It is expected that the results presented in this article may be useful for improving the renewable energy development policy both at the country level and at the level of a particular economic entity.